Impact of Pre-pregnancy Body Mass Index on Neonatal Outcome - Anchala Bhardwaj; Ruchi Rai (Mashhad University of Medical Sciences, 2021)
Background: Pre-pregnancy body mass index (BMI) during the gestation period is a major factor that predicts fetal weight and development. It is also positively associated with an increase in fetal head circumference and femur length. To assess the impact of pre-pregnancy BMI on neonatal anthropometryMethods: This multicenter observational study was conducted from July 2010-July 2011. A total of 1,000 mothers were enrolled, and their antenatal records were screened for pre-pregnancy weight, height, and other details. They were assigned to four categories as per their BMI: underweight: BMI<18.5kg/m2, normal:18.5-24.99kg/m2, overweight: 25-29.9kg/m2, and obese: ≥30kg/m2 group. The neonatal anthropometric measurements and other information were retrieved from the neonate's files. Neonates who were admitted to the neonatal intensive care unit (NICU) were followed till their discharge from hospital or mortality.Results: Out of 1,000 cases, 170 (17%) belonged to underweight, 224 (22.4%) to overweight, 86 (8.6%) to obese, and 520 (52%) to the normal group. Overweight and obese women were at a higher risk of developing gestational diabetes mellitus, hypertensive complications during pregnancy, and undergoing cesarean sections. They also had a higher risk of delivering large for gestational age and post-term neonates, whereas underweight women had a significantly higher risk of delivering small for gestational, low birth weight, and premature newborns. Furthermore, a positive correlation was observed between maternal BMI and neonatal anthropometric measurements.Conclusion: As evidenced by the obtained results, both low and high pre-pregnancy BMI is associated with adverse maternal and perinatal outcomes.